ANALISIS DALAM MENENTUKAN STOK BARANG MASUK DARI SUPPLIER PADA BLIBLI.COM MEDAN MENGGUNAKAN METODE ASSCOATION RULE DENGAN ALGORITMA APRIORI - Delima Sitanggang; Oktoberto Perangin-angin; Esther Mayorita Nababan; Meri Natasia Napitupulu; Evta Indra (Politeknik Bisnis Indonesia, 2023)
The divisions that support the service production business continue to be developed, so as to provide more benefits for the organizers. One part that continues to be researched is the determination of suppliers of goods for production companies, because a good supplier will not only maximize cooperative relations, but also supply quality raw materials, as well as provide convenience in the process of importing goods. in the previous calculations the minimum support value that had been determined was 3.5%, so the researcher formed 1 itemset where the support value met the percentage in the category (accessories 5.8%), (cigarette 11.4%), (cooking ingredients 23.1%), (electronic 30.9%), (food 28.1%), (gagdet,46.6%), (healthy&beauty 12.4%), and y(kids&baby 4.2%) , in the formation of 2 itemsets where those containing A are combined with those containing item B which fulfill the percentages on (electronics, food 19.3%) , (gadgets, cooking ingredients 23.9%), (gagdet, electronics 37.6%) , and (gagdet, food 19.3%) in the formation of 3 itemsets with support (A,B,C) there is no item value that meets the minimum support value and for the minimum confidence value in this study 40% in the establishment of a rule or association of 2 itemsets that meet confidence (cigarettes, kids baby 52.6%), and (kids babies, accessories 47.6%), for the establishment of a 3 itemset association rule that meets the minimum confidence value (kids babies, electronics, accessories 47.6%), (kids baby, fozen food, accessories 47.6%), (food, gadgets, kids baby 95.2%), (kids baby, fozen food, cooking ingredients 47.6%).